A method for preparing fruit wood-based hard carbon negative electrode material for sodium ion battery
Through the preparation method of fruit wood-based hard carbon anode material, the existing sodium ion battery hard carbon anode material has been solved, and the hard carbon material with high capacity, high first efficiency and excellent circulation performance has been achieved. , improves the overall performance and safety of the battery.
Patent Information
- Application Number
- CN202410933295.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The existing sodium ion battery hard carbon anode materials have low sodium storage capacity, poor first-effect and battery capacity, and are prone to peeling and powdering during charging and discharging, affecting conductivity and safety.
Using the preparation method of fruit wood-based hard carbon anode material, high-capacity and high-first-effect hard carbon materials are developed through pre-carbonization, purification, element doping, high-temperature carbonization, interface structure and gas activation.
It realizes hard carbon materials with high capacity, high first-term efficiency and excellent cycle performance, with a charging specific capacity of 300-450mAh/g, with a first-term effect of ≥90%, and effectively prevents peeling and powdering, improving conductivity and safety .
Smart Images

Figure CN118598134B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery electrode materials, and in particular to a method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery. Background Art
[0002] In recent years, with the rapid development of science and technology and the improvement of human living standards, fossil energy has been consumed in large quantities, and the energy shortage problem has become increasingly serious. Therefore, people's demand for clean and renewable energy is increasing, and at the same time, the requirements for large-scale, efficient and cheap energy storage systems are also increasing. Lithium-ion batteries (LIBs) have the advantages of high energy density and long cycle life, and have been widely used in portable electronics and electric vehicle markets. However, the limited and uneven distribution of lithium resources restricts its application in the field of large-scale energy storage.
[0003] Compared with lithium-ion batteries, sodium-ion batteries are gradually becoming a choice in the field of large-scale energy storage due to their abundant sodium resources, similar working principles to LIBs, low cost, good low-temperature performance and fast charging performance. They can also serve as a low-cost supplement to lithium-ion batteries. Although several positive electrode materials for sodium-ion batteries (such as layered oxides, polyanionic compounds, and Prussian blue) have been well developed, there are still certain challenges in developing sodium-ion battery negative electrodes with high sodium storage capacity and low cost and high performance.
[0004] Among many carbon-based materials, hard carbon has a low sodium insertion potential, high reversible capacity, good electrical conductivity, and a wide range of synthetic raw materials and low prices, which has attracted the attention of many scientific researchers. However, the initial efficiency and battery capacity of hard carbon negative electrode materials are currently low, and the charging performance, conductivity and safety performance are poor, and the use effect is not ideal. Summary of the invention
[0005] The purpose of the present invention is to solve the above-mentioned problems and provide a method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery which can obtain a high capacity and high initial efficiency hard carbon negative electrode material, and the hard carbon negative electrode material has high surface strength and strong toughness, can effectively prevent peeling and pulverization during the charging and discharging process, and improves the overall conductivity and safety.
[0006] To achieve the above-mentioned purpose, the technical scheme of the present invention is: a method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1: pre-carbonization: pre-carbonizing the fruit wood under an inert gas to obtain a hard carbon precursor; S2: coarse crushing: coarse crushing the pre-carbonized material in step (1) to obtain a precursor material with a suitable particle size; S3: purification and drying: adding the precursor in step (2) to an HCl solution and stirring for 24 hours, washing with water to neutrality, and drying in an oven at 105°C to obtain a purified precursor; S4: mixed batching and element doping: taking the purified precursor, phosphorus-containing reagent, and nitrogen-containing reagent and mixing them evenly in a ball mill to obtain a mixed batch and element-doped precursor material; S5: High-temperature carbonization: Under nitrogen atmosphere, the precursor in step (4) is placed in a high-temperature carbonization furnace for high-temperature carbonization to obtain a high-temperature carbonized precursor; S6: Interface construction: The high-temperature carbonized precursor and the coating agent are mixed evenly in a VC high-speed mixer; At a certain temperature, the mixed material is carbonized in nitrogen gas, and a hard carbon precursor with a core-shell structure is obtained when the temperature drops to room temperature; S7: Gas activation: In the activation gas, a certain mass of the hard carbon precursor with a core-shell structure is placed in a hydrogen-argon mixture at a certain temperature for activation, and the corresponding hard carbon material is obtained when the temperature drops to room temperature.
[0007] Preferably, the pre-carbonization temperature in step S1 is 400-800°C, the holding time is 1-8h, and the heating rate is 1-10°C / min; the protective gas used for carbonization is one or more of inert gases such as nitrogen, argon, helium, neon, etc.
[0008] Preferably, the fruit wood in step S1 includes lychee wood, apple wood, jujube wood, pear wood, peach wood, walnut wood, apricot wood, citrus wood, hawthorn wood, longan wood, mango wood, durian wood, olive wood, carambola wood, orange wood, lemon wood, cherry wood, grapefruit wood, pomegranate wood, loaf wood, bayberry wood, plum wood, carambola wood or jujube wood.
[0009] Preferably, the pulverizing equipment in step S2 includes one or more of a fluidized bed air flow mill, a target air flow mill, a flat air flow mill, a circulating tubular air flow mill, a jet air flow mill, and a fluidized bed air flow mill.
[0010] Preferably, the purification in step S3 is alkali washing or acid washing, the alkali in the alkali washing is an organic alkali or an inorganic alkali, the organic alkali is sodium methoxide, potassium ethoxide, potassium tert-butoxide, an alkyl lithium reagent, a Grignard reagent or a quaternary ammonium hydroxide salt, and the inorganic alkali is sodium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, sodium thiosulfate, sodium hydroxide, lithium hydroxide, potassium hydroxide, ammonia water, ammonia methanol solution or ammonium bicarbonate; the acid in the acid washing is an organic acid or an inorganic acid, the organic acid is carboxylic acid (R-COOH), sulfonic acid (R-SO3H), sulfinic acid (R-SOOH), thiocarboxylic acid (R-SH), citric acid, malic acid, tartaric acid, acetic acid, succinic acid, oxalic acid or quinic acid, and the inorganic acid is hydrochloric acid, sulfuric acid, nitric acid, boric acid, carbonic acid or phosphoric acid.
[0011] Preferably, in S4, the phosphorus-containing reagent is one or more of phosphorus powder, phosphoric acid, monocyanammonium phosphate, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate, and the nitrogen-containing reagent is one or more of melamine, urea, ammonium nitrate, ammonium dihydrogen phosphate, aniline, ammonium chloride, pyridine, p-nitroaniline, triethylamine, sodium nitrate, and potassium nitrate.
[0012] Preferably, in step S5, the high-temperature carbonization furnace is one or more of a box furnace, an Acheson furnace, an inner string furnace, a drum furnace, a roller kiln, a push plate kiln, and a medium frequency furnace, the high-temperature carbonization gas is one or more of nitrogen, argon, helium or neon, the high-temperature carbonization temperature is 1000-1600°C, and the heating rate is 1-10°C / min.
[0013] Preferably, the coating agent in step S6 is low-temperature coal tar or petroleum asphalt, medium-temperature coal tar or petroleum asphalt, high-temperature coal tar or petroleum asphalt with different softening points and different coking values, or liquid phenolic resins with different viscosities.
[0014] Preferably, the activation gas in step S7 is one or more of a hydrogen-argon mixed gas and a hydrogen-nitrogen mixed gas.
[0015] Preferably, the surface area of the hard carbon material in step S7 is 0.5-30 m 2 / g, tap density is 0.5-1.5cm 3 / g, the interlayer spacing is 0.36-0.42nm, and the hard carbon material is used as the negative electrode of the sodium ion battery. When the current density is 30mA / g, the charging specific capacity is 300-450mAh / g, and the first efficiency is ≥90%.
[0016] The method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery disclosed in the present invention has the following beneficial effects compared with the prior art:
[0017] (1) The fruit wood-based hard carbon negative electrode material provided by the present invention uses a large amount of pruned and withered fruit wood as a hard carbon precursor, realizing high value-added utilization of waste wood, truly turning waste into treasure;
[0018] (2) The preparation method provided by the present invention develops a hard carbon material that can be commercialized on a large scale by purifying the fruit wood precursor, regulating the crystal structure, designing the morphology and reconstructing the interface. When it is used as a negative electrode material for sodium ion batteries, the charging capacity can reach 300-450mAh / g at a current density of 20mA / g, and the first efficiency is ≥90%. The capacity retention rate after 1000 cycles at a 1C / 1C rate is about 80-95%;
[0019] (3) The present invention uses coating means to reconstruct the hard carbon interface, which effectively reduces the specific surface area of the hard carbon material, enhances the structural stability of the hard carbon material, greatly reduces the formation of the SEI film, and improves the first coulomb efficiency; in addition, by regulating the oxygen-containing functional groups of the material, more defect sites are formed, thereby increasing more active sites;
[0020] (4) The present invention uses N and P element doping to precisely regulate the interlayer spacing of hard carbon by controlling the amount of doping elements and the corresponding high-temperature carbonization temperature, thereby obtaining a larger interlayer spacing and a suitable crystal size, achieving rapid intercalation and deintercalation of sodium ions between the layers, and ultimately improving the specific capacity and rate performance of the material.
[0021] (5) The present invention provides a sodium ion battery fruit wood-based hard carbon negative electrode material and a preparation method thereof, which uses fruit wood as a precursor, has low cost, simple process, and is easy to industrialize and mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the hard carbon obtained in Example 1.
[0023] Figure 2 This is the SEM image of the hard carbon obtained in Example 2. DETAILED DESCRIPTION
[0024] The present invention will now be described in further detail with reference to the accompanying drawings. The accompanying drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and thus only show the components related to the present invention.
[0025] See also Figure 1 The present invention discloses a method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0026] S1 Pre-carbonization: In a nitrogen atmosphere, 20 kg of lychee wood with a length of 2-40 cm was pre-carbonized at 600°C for 4.0 h to obtain a hard carbon precursor; the heating rate of the pre-carbonization process was 3°C / min.
[0027] S2 coarse crushing: coarsely crushing the pre-carbonized material in step (1) to obtain a precursor material with a median particle size (D50) of 6.0±1.0 μm;
[0028] S3 purification and drying: the precursor in step (2) was added to a 4.0 M HCl solution, heated at 60°C with stirring for 24 h, washed with water until neutral (PH = 7) and dried in an oven at 105°C for 4.0 h to obtain a purified precursor;
[0029] S4 mixed batch, element doping: 4.0 kg of purified precursor, 0.4 kg of melamine, and 0.4 kg of diammonium phosphate (the mass ratio of the purified precursor, melamine, and diammonium phosphate is 10:1:1) are taken and mixed evenly in a ball mill to obtain mixed batch and element doping precursor materials;
[0030] S5 high temperature carbonization: under nitrogen atmosphere, the precursor in step (4) is placed in a high temperature carbonization furnace at 1400°C for 6.0 hours at a heating rate of 2°C / min, and the temperature is lowered to room temperature to obtain a high temperature carbonized precursor;
[0031] S6 interface structure: 3.0Kg of high-temperature carbonized precursor and 0.15Kg of asphalt (softening point is 250°C) are mixed evenly in a VC high-speed mixer (the mass ratio of the high-temperature carbonized precursor to asphalt is 20:1), and the speed of the VC high-speed mixer is 200RPM; the mixed material is kept at 1200°C for 2.0h under a nitrogen atmosphere, and the heating rate is 2°C / min, and the hard carbon precursor with a core-shell structure is obtained when the temperature drops to room temperature;
[0032] S7 gas activation: In a hydrogen-argon mixed gas atmosphere (wherein the volume ratio of hydrogen to argon is 1:10), 2.5 kg of the core-shell structure hard carbon precursor was placed in a hydrogen-argon mixed gas at 300 °C for activation for 2.0 h. The heating rate during activation was 2 °C / min. When the temperature dropped to room temperature, the corresponding hard carbon material was obtained, which was recorded as TLZ-1400-300. Figure 1 This is the scanning electron microscope image of Example 1.
[0033] See also Figure 2 The present invention discloses a method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0034] The fruit wood used in this embodiment 2 is apple wood. Except for the different fruit wood, the other steps of embodiment 2 are the same as those of embodiment 1, and the material is recorded as TPG-1400-300.
[0035] Embodiment 3:
[0036] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0037] The fruit wood used in this embodiment 3 is jujube wood. Except for the different fruit wood, the other steps of embodiment 3 are the same as those of embodiment 1, and the material is recorded as TZM-1400-300.
[0038] Embodiment 4:
[0039] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0040] The fruit wood used in this embodiment 4 is pear wood. Except for the different fruit wood, all other steps in embodiment 4 are the same as those in embodiment 1, and the material is recorded as TLM-1400-300.
[0041] Embodiment 5:
[0042] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0043] The fruit wood used in this embodiment 5 is peach wood. Except for the different fruit wood, the other steps of embodiment 5 are the same as those of embodiment 1, and the material is recorded as TTM-1400-300.
[0044] Embodiment 6:
[0045] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0046] The fruit wood used in this embodiment 6 is apricot wood. Except for the different fruit wood, all other steps in embodiment 6 are the same as those in embodiment 1, and the material is recorded as TXM-1400-300.
[0047] Embodiment 7:
[0048] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0049] The fruit wood used in this Example 7 is citrus wood. Except for the different fruit wood, all other steps in Example 7 are the same as those in Example 1, and the material is recorded as TGJ-1400-300.
[0050] Embodiment 8:
[0051] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0052] The fruit wood used in this Example 8 is longan wood. Except for the different fruit wood, all other steps in Example 8 are the same as those in Example 1, and the material is recorded as TGY-1400-300.
[0053] Comparative Example 1:
[0054] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0055] Compared with Example 1, the steps of Comparative Example 1 are the same as those of Example 1 except that purification and drying are not performed, and are not described here; the final material is recorded as NTLZ-1400-300.
[0056] Comparative Example 2:
[0057] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0058] Compared with Example 1, the steps of Comparative Example 2 are the same as those of Example 1 except that the interface construction is not performed, and are not described here; the final material is recorded as LZ-1400-300.
[0059] Comparative Example 3:
[0060] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0061] Compared with Example 1, the steps of Comparative Example 3 are the same as those of Example 1 except that the gas activation is not performed, and the details are not repeated here; the final material is recorded as TLZ-1300.
[0062] Comparative Example 4:
[0063] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0064] Compared with Example 1, in Comparative Example 4, except that the mixed batch and element doping steps are not performed, the other steps are the same as those of Example 1, which are not repeated here; the final material is recorded as NYLZ-1400-300.
[0065] Comparative Example 5:
[0066] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0067] Compared with Example 1, in Comparative Example 5, except that the high-temperature carbonization temperature is changed to 1300° C., the other steps are the same as those of Example 1, which will not be repeated here; the final material is recorded as TLZ-1300-300.
[0068] Comparative Example 6:
[0069] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0070] Compared with Example 1, in Comparative Example 6, except that the high-temperature carbonization temperature is changed to 1500° C., the other steps are the same as those of Example 1, which will not be repeated here; the final material is recorded as TLZ-1500-300.
[0071] Comparative Example 7:
[0072] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0073] Compared with Example 1, the steps of Comparative Example 7 are the same as those of Example 1 except that the high-temperature carbonization temperature is changed to 1600° C., and are not repeated here; the final material is recorded as TLZ-1600-300.
[0074] Comparative Example 8:
[0075] A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0076] Compared with Example 1, in Comparative Example 8, except that the high-temperature carbonization temperature is changed to 1800° C., the other steps are the same as those of Example 1, which will not be repeated here; the final material is recorded as TLZ-1800-300.
[0077] The physical and chemical indicators of the specific embodiments and comparative examples are shown in the following table:
[0078]
[0079] The hard carbon negative electrode materials obtained in Examples 1 to 8 and Comparative Examples 1 to 8 were mixed in pure water according to the mass ratio of hard carbon material, conductive carbon black and binder of 94:2.5:3.5, homogenized, and the solid content was controlled to be about 33%. The mixture was coated on an aluminum foil current collector, vacuum-baked at 80°C for 12 hours, and pressed into shape. The negative electrode sheets were prepared by punching. Button cells were assembled in a glove box filled with argon. The counter electrode was a metal sodium sheet, the diaphragm used was a glass fiber diaphragm, and the electrolyte was EC / DMC (Vol1:1) of NaPF6. The button cells were charged and discharged using a Xinwei battery test system. The voltage range was 0.0V-2.0V and the current density was 30mA / g. The first reversible capacity and efficiency of the hard carbon negative electrode materials in the Examples and Comparative Examples were measured as shown in Table 1.
[0080] Through the analysis of Examples 1-8, it can be known that a high-capacity, high-initial-efficiency hard carbon product can be obtained by purification, element doping, interface modification and gas activation of the fruit wood-based precursor; wherein the interface structure can reduce the specific surface area of the material, effectively prevent the peeling and pulverization of the hard carbon during the charge and discharge process, and improve the electrochemical performance; after the asphalt is coated on the negative electrode, a high-strength and high-toughness coating layer is formed, which is combined with the negative electrode after carbonization to form a dense protective layer of hard carbon and soft carbon, which not only repairs the surface defects of the negative electrode, but also has good compatibility with the electrolyte. The isotropy of the coating layer and the surface structure characteristics of hard carbon and soft carbon can greatly improve the fast charging performance, cycle performance, conductivity and safety performance of the battery.
[0081] Compared with Example 1, the capacity (350.67 mAh / g) and first efficiency (78.9%) of Comparative Example 1 are lower than those of Example 1 (410.35 mAh / g) and first efficiency (91.3%), which shows that pickling has a greater impact on the electrical properties of the material; pickling can remove a large amount of metal ions and metal oxides, thereby improving the purity of the material and optimizing the performance of the material; Compared with Examples 1-8, the material obtained in Comparative Example 2 has no interface structure, has more surface defects, and has poor performance; At the same time, Comparative Example 4 can be compared with Examples 1-8. It is known that element doping can greatly improve the performance of materials; the introduction of heteroatoms can cause changes in the microstructure of materials. Usually, the introduction of P atoms can effectively change the interlayer spacing, electronic conductivity, wettability of the hard carbon material surface, etc., thereby improving the electrical properties of materials; compared with Example 1, the carbonization temperatures of materials in Comparative Examples 5-8 are different; from the comparison, it can be seen that the higher the carbonization temperature, the better the performance of the material; a higher carbonization temperature will lead to a decrease in the interlayer spacing of the material, which is not conducive to the migration of sodium ions; so the appropriate carbonization temperature and heating rate also play a key role in the performance of the electrical properties of the material.
[0082] The hard carbon negative electrode material prepared by the method of the present invention can be used in sodium ion batteries, lithium ion batteries or potassium ion batteries.
[0083] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a fruit wood-based hard carbon negative electrode material for a sodium ion battery, characterized in that: The method comprises the following steps: S1: pre-carbonization: pre-carbonizing the fruit wood at a temperature of 400-800° C. under an inert gas to obtain a hard carbon precursor; S2: Coarse crushing: Coarsely crushing the pre-carbonized material in step (1) to obtain a precursor material with a suitable particle size; S3: Purification and drying: adding the precursor in step (2) into the acid washing solution and stirring for 24 hours, washing with water until neutral, and drying in an oven at 105°C to obtain a purified precursor; S4: Mixed batch and element doping: take the purified precursor, phosphorus-containing reagent, and nitrogen-containing reagent and mix them evenly in a ball mill to obtain a mixed batch and element doped precursor material; S5: High temperature carbonization: under nitrogen atmosphere, the precursor in step (4) is placed in a high temperature carbonization furnace for high temperature carbonization to obtain a high temperature carbonized precursor; S6: Interface construction: Take the high-temperature carbonization precursor and the coating agent in a VC high-speed mixer and stir them evenly; at a certain temperature, carbonize the mixed material in a nitrogen atmosphere, and wait for the temperature to drop to room temperature to obtain a hard carbon precursor with a core-shell structure; the coating agent is low-temperature coal tar or petroleum asphalt, medium-temperature coal tar or petroleum asphalt, high-temperature coal tar or petroleum asphalt with different softening points and different coking values, and liquid phenolic resins with different viscosities; S7: Gas activation: In the activation gas, place a certain mass of core-shell structured hard carbon precursor in a hydrogen-argon mixture at a certain temperature for activation, and wait for the temperature to drop to room temperature to obtain the corresponding hard carbon material.
2. The method for preparing the fruit wood-based hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: In the step S1, the pre-carbonization temperature is 600°C, the holding time is 1-8h, and the heating rate is 1-10°C / min; the protective gas used for carbonization is one or more of nitrogen, argon, helium, and neon.
3. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: The fruit wood in step S1 includes lychee wood, apple wood, jujube wood, pear wood, peach wood, walnut wood, apricot wood, citrus wood, hawthorn wood, longan wood, mango wood, durian wood, olive wood, carambola wood, orange wood, lemon wood, cherry wood, grapefruit wood, pomegranate wood, loaf wood, bayberry wood, plum wood, carambola wood or jujube wood.
4. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: The pulverizing equipment in step S2 includes one or more of a fluidized bed jet mill, a target jet mill, a flat jet mill, a circulating tubular jet mill, a jet mill, and a fluidized bed jet mill.
5. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: The purification in step S3 is pickling, the pickling solution is an organic acid or an inorganic acid, the organic acid is carboxylic acid (R-COOH), sulfonic acid (R-SO3H), sulfinic acid (R-SOOH), thiocarboxylic acid (R-SH), citric acid, malic acid, tartaric acid, acetic acid, succinic acid, oxalic acid or quinic acid, and the inorganic acid is hydrochloric acid, sulfuric acid, nitric acid, boric acid, carbonic acid or phosphoric acid.
6. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: In S4, the phosphorus-containing reagent is one or more of phosphorus powder, phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate, and the nitrogen-containing reagent is one or more of melamine, urea, ammonium nitrate, ammonium dihydrogen phosphate, aniline, ammonium chloride, pyridine, p-nitroaniline, triethylamine, sodium nitrate, and potassium nitrate.
7. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: In step S5, the high-temperature carbonization furnace is one or more of a box furnace, an Acheson furnace, an inner string furnace, a drum furnace, a roller kiln, a push plate kiln, and a medium frequency furnace; the high-temperature carbonization gas is one or more of nitrogen, argon, helium or neon; the high-temperature carbonization temperature is 1000-1600°C, and the heating rate is 1-10°C / min.
8. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: In step S7, the activation gas is one or more of a hydrogen-argon mixed gas and a hydrogen-nitrogen mixed gas.
9. The method for preparing the fruit wood-based hard carbon negative electrode material for ion batteries according to claim 1, characterized in that: The surface area of the hard carbon material in step S7 is 0.5-30m 2 / g, tap density is 0.5-1.5cm 3 / g, the interlayer spacing is 0.36-0.42nm, and the hard carbon material is used as the negative electrode of the sodium ion battery. When the current density is 30mA / g, the charging specific capacity is 300-450mAh / g, and the first efficiency is ≥90%.
Citation Information
Patent Citations
Element-doped biomass hard carbon negative electrode material for sodium-ion battery, preparation method and sodium-ion battery
CN110571432A
Biomass hard carbon negative electrode material of sodium ion battery and preparation method of biomass hard carbon negative electrode material
CN113206246A